(untitled) (Biological Sciences - PJSIR, 2011)
The effects of using different concentrations of chemically and physically modified water chestnut (Trapa bispinosa) starch (WCS) on loaf weight, volume and specific volume of yeast leavened bread were studied. The highest loaf weight was obtained by the addition of native water chestnut starch at 3 % concentration, while the opposite effect was observed regarding the loaf volume and specific volume. The highest loaf volume and the specific volume was obtained on addition of WCS, pregelatinized and acetylated (pga), at 1% concentration. Maximum mean score (7.8) was obtained by native water chestnut starch at concentration of 5% and minimum mean score was obtained by pgaWCS at 1% concentration with respect to the taste of bread. Regarding the texture, the maximum mean score (7.5) was that of the bread containing 5% pga (pregelatinized and acid thinned) WCS and minimum mean score (4), that of the bread containing 5% acetylated water chestnut starch.